The vulnerability of migrants from Bulgaria to human trafficking for labor exploitation - Stamenkov, Radoslav Tihomirov (Dve domovini, 2025)
The article analyzes the vulnerability of labor migrants from Bulgaria to traffickers and exploiters. Based on in-depth interviews with victims and experts in the field of human trafficking, the authors identify the main factors for falling into trafficking and the methods of recruiting and exploiting victims. The article answers the question as to why this phenomenon remains so persistent over time. A worrisome trend has been observed where victims perceive exploitation as a regular aspect of their employment abroad. The authors point out that reducing migrants’ vulnerability largely depends on the broader national socioeconomic context, global inequalities, and the demand for cheap labor.
Keywords: Bolgari; Bolgarija; Bulgaria; Bulgarians; human trafficking; izkoriščanje delovne sile; labour exploitation; migracije; migration; trgovina z ljudmi